Motivation and attitude of English language learning among nursing students - Dior Manta Tambunan; Yetty Mariani Tambun; Sridama Yanti Harahap (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Proficiency in speaking English is an individual's ability to convey thoughts and desires verbally to anyone. However, it can be challenging to develop this skill without continuous self-training. One effective approach is through peer or classmate interactions, as well as guidance from English language instructors. Numerous factors influence the success of students in learning English, and motivation and attitude are crucial aspects needed by nursing students to master the language.Purpose: To identify the description of motivation and attitude among nursing students in learning English, providing input for learning achievement targets for English courses and the most suitable learning methods to enhance the language skills of nursing students at Murni Teguh University.Method: A quantitative research method with a descriptive design was employed. The total sampling technique was used, and 157 respondents willingly filled out the questionnaire from a total population of 167 individuals. Instruments for measuring motivation and attitude were adopted from previous studies with established validity. Data analysis utilized Univariate data analysis.Results: Instrumental motivation among respondents (90.5%) was higher than integrative motivation (88.9%). The majority of respondents had high motivation at 89.6%. Meanwhile, most respondents exhibited good attitudes at 41.2%, followed by fairly good attitudes at 36.4%, and poor attitudes at 22.4%.Conclusion: Nursing students at Murni Teguh University demonstrate high motivation and positive attitudes toward learning English. However, this does not align with the English language proficiency of the respondents.Suggestion: It is highly recommended for future researchers to include additional variables such as interest in learning, self-concept, self-efficacy, the cause-and-effect correlation between each researched variable in English language learning, and the use of effective English teaching methods to enhance the English language proficiency of nursing students.